Mishaps, errors, and cognitive experiences: on the conceptualization of perceptual illusions - Zavagno, Daniele; Daneyko, Olga; Actis-Grosso, Rossana (Frontiers in Human Neuroscience, 2015)
Although a visual illusion is often viewed as an amusing trick, for the vision scientist it is a question that demands an answer, which leads to even more questioning. All researchers hold their own chain of questions, the links of which depend on the very theory they adhere to. Perceptual theories are devoted to answering questions concerning sensation and perception, but in doing so they shape concepts such as reality and representation, which necessarily affect the concept of illusion. Here we consider the macroscopic aspects of such concepts in vision sciences from three classic viewpoints – Ecological, Cognitive, Gestalt approaches – as we see this a starting point to understand in which terms illusions can become a tool in the hand of the neuroscientist. In fact, illusions can be effective tools in studying the brain in reference to perception and also to cognition in a much broader sense. A theoretical debate is, however, mandatory, in particular with regards to concepts such as veridicality and representation. Whether a perceptual outcome is considered as veridical or illusory (and, consequently, whether a class of phenomena should be classified as perceptual illusions or not) depends on the meaning of such concepts.